In memory of Beethovenfest Bonn 1871 - Unknown:::Creator::::::::::::
Visiting card for the Beethoven festival in Bonn in 1871, with portraits of Frau Schreck, Dr. F. Hiller, Melita Otto Alvsleben, Frau Joachim, V. Wasielewsky, AD Schulze, Charles Halle, Vogl, and L. van Beethoven.